Explaining Manufacturing and Non‐Manufacturing Inbound FDI Location in Five UK Regions. (22nd November 2013) - Fallon, Grahame; Cook, Mark
Abstract This paper extends the analysis of foreign direct investment (FDI) location in the UK by exploring the determinants of manufacturing and non‐manufacturing inbound FDI location within and between the UK's core (the Southeast) and non‐core (West Midlands; Wales; Scotland and the Northwest) regions. Use is made of multiple regression techniques to analyse a set of official, longitudinal data gathered for the period from 1980 to 2005 as a means to this end. The findings offer new insights into the relative influence of regional, national and EU level factors and government policy over FDI location at the UK regional level, and into their variation between regions and sectors of industry. The resultant implications for government policies towards inbound FDI are also considered, including the desirability of allowing them to vary from region to region, if FDI inflows are to be maximised.